Upaya Meningkatkan Strategi Pengembangan Usaha Olbi Kreasi - Januarty, Tamy Ali; Rahman, Melinda; Nurmansyah, Abdul Ahmad Hafidh (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2022)
In the era of rapid development of digital technology as it is today, marketing activities and business book keeping can be done digitally. In preparing financial statements that have limitations in financial recording. We conduct training on how to increase sales with digital marketing and the use of the “buku kas” Application for Compiling Financial Statements via online zoom. The “buku kas” application is one of the bookkeeping applications available on Android and IOS. After implementing digital marketing, partners can reach more potential consumers. The 'buku kas' application has also succeeded in making partners prepare financial reports faster and easier.